Expanding horizon of invasive alien plants under the interacting effects of global climate change: Multifaceted impacts and management prospects - Roger Bruce Syngkli; Prabhat Kumar Rai; Lalnuntluanga (Climate Change Ecology)
Anthropogenic disturbances driven introduction of invasive alien plants (IAP) threatened the native biodiversity and environmental sustainability. IAP induced biotic homogenization can also disrupt ecosystem functioning/-services and socio-economy. Multifaceted threats of IAP can further be exacerbated under the interactive effects of climate change. However, IAP-climate change interaction is insufficiently addressed. Therefore, present review attempts to explicitly elucidate this linkage for cross-sectoral invasion ecology and management research. Changes in climatic variables also facilitated IAP to expand their horizon irrespective of the extreme climate and geographical barriers, which enhanced the vulnerability of protected areas rich in endemics. Moreover, IAP-climate change impacted the forestry/agroforestry systems by restricting abiotic resources and influencing forest regeneration, litter stock, and nutrient cycling. Consequently, IAP-climate change can influence ecological economics, livelihood, and human well-being. Implementation of species distribution model (SDM) into management and mitigation strategies is required to control IAP along with the present and future climate change scenarios.